Who are we now? Christian humanism and the global market from Hegel to Heaney - Boyle, Nicholas 1946- (Univ. of Notre Dame Press, 1998)
In this book, Nicholas Boyle offers ten studies of the implications of the increasingly integrated world economic structure for our sense of political, cultural, and personal identity. He argues for the deep interconnectedness of politics, religion, philosophy, and literature and their shared inseparability from the economic base. In the process, he uses philosophical and literary ideas to establish systematic grounds for optimism about an emerging supra-national order, aiming to restore the possibility of "grand narrative" to our collective past and future. Boyle takes a close look at Germany and Britain, their differences and growing similarity. He discusses, among others, Thatcher, Fukuyama, Hegel, Nietzsche, Heidegger, Derrida, and Seamus Heaney. Boyle asserts that as the world becomes less divided but more disparate, and its order less draconian but more precarious, choosing the paths most likely to lead to justice and peace will reform our shattered sense of identity.
Keywords: Geschichte 1900-2000; Geschichte 1989-1996; Geschichte; Intellectual life -- History -- 20th century; Postmodernism; World politics -- 1989-; Internationale Politik; Postmoderne